TRANSFORMASI EKONOMI LOKAL MELALUI PENGUATAN INDUSTRI HALAL DI PADANG LAWAS UTARA - hardana, ali; Damisa, Arti (Jurnal Masharif al-Syariah: Jurnal Ekonomi dan Perbankan Syariah, 2025)
This study aims to analyze local economic transformation through the strengthening of the halal industry in Padang Lawas Utara Regency. The background of this research stems from the growing public awareness of halal products and the significant potential of the halal sector in promoting regional economic growth. However, the development of the halal industry in Padang Lawas Utara still faces several challenges, including limited infrastructure, low halal literacy among business actors, and the suboptimal implementation of local government policies. This research employs a qualitative descriptive approach with data collected through in-depth interviews, field observations, and document studies involving MSME actors, government officials, and community leaders. The results indicate that strengthening the halal industry plays a crucial role in creating economic added value, expanding employment opportunities, and enhancing regional competitiveness. Furthermore, synergy among the government, Islamic financial institutions, and business actors is identified as a key factor in accelerating local economic transformation based on halal and sustainable principles.